Adult Chinese Spanish L2ers’ acquisition of phi-agreement and temporal concord: The role of morphosyntactic features and adverb/subject-verb distance - Mao, Tiaoyuan; Biondo, Nicoletta; Zheng, Zilong (Frontiers in Psychology, 2022)
While phi-agreement and concord are suggested to differ in nature during the first language (L1) acquisition, the acquisition of adverb-verb TC and SV person/number agreement by Chinese Spanish second language (L2) learners has only received limited attention. The current study examined morphosyntactic processing by advanced Chinese Spanish L2 learners (L2ers), whose L1 lacks the explicit morphological marking of tense and phi-agreement. The results of a self-paced grammaticality judgment task show that for both Spanish L1 speakers and L2ers, SV agreement violations are detected earlier and judged more accurately than adverb-verb TC violations, suggesting that different cognitive mechanisms are at play during phi-agreement and concord computations. Moreover, L2ers process SV number agreement less efficiently than SV person agreement (but as efficiently as adverb-verb TC), indicating that they might have problems with the [Number] feature. The findings imply that L2ers’ sensitivity to grammatical errors changes as a function of the morphosyntactic feature(s) involved.